Integrating leaf optical sensing with canopy structure improves nitrogen diagnosis in drip-irrigated maize - Weidong Ma; Xinjiang Zhang; Haiting Su; Guoyong Chen; Zaixin Li; Xuezhi Zhang; Zhenbo Sun; Xiangnan Li; Zixin He; Changzhou Wei (European Journal of Agronomy, 2026)

Effect of chitosan nanocarriers on the interaction between cimetidine and bovine serum albumin and its regulation of protein conformation - Shijun Yu; Jiawei Huang; Haiting Sun; Jiali Gu (Chemico-Biological Interactions, 2026)

Metabolism-dependent induction of DNA and chromosome damage by orally administered carbamazepine in adult male C57BL/6J mice, Cyp2b being major activating enzymes - Haiting Sun; Manxin Chen; Shunda Zhu; Ke Xu; Yujian Wang; Yungang Liu (Archives of Toxicology, 2026)

Potent genotoxicity of phenytoin in adult male C57BL/6J mice, an effect requiring metabolic activation (possibly by Cyp2c enzymes) - Manxin Chen; Haiting Sun; Shunda Zhu; Hang Yu; Yungang Liu (Chemico-Biological Interactions, 2026)

Bias-tunable multifunctional optoelectronic logic gate based on Cs2AgBiBr6 photodetector for binary coding communication and human visual bionic - Chaoyang Li; Liping Liu; Ruihuan Zhang; Tianchen Ji; Jing Zhao; Jiaxing Sun; Xun Liu; Haiting Zhang; Xuanqi Zhong; Xiaoxian Song; Jingjing Zhang; Zijie Dai; et al. (Chemical Engineering Journal, 2025)

Prevalence and spectrum of STRC variants in 1015 sensorineural hearing loss patients: insights from the Chinese population - Luo Guo; Sha Yu; Wenrui Zhao; Liheng Chen; Guiqing Cheng; Weitao Li; Wei Li; Haiting Ji; Shan Sun; Huiqian Yu; Haiying Liu; Chunyi Gui; et al. (Molecular Genetics and Genomics, 2025)

Prediction of polybrominated diphenyl ethers (PBDEs) as potential substrates of various human CYP enzymes and laboratory test of BDE-99 for its metabolism-activated mutagenicity - Lin Wang; Nyame Mustapha Murtala; Keqi Hu; Yijing Chen; Manxin Chen; Haiting Sun; Yungang Liu (Toxicology, 2024)

Breast cancer therapy: from the perspective of glucose metabolism and glycosylation - Jiaqi Zhao; Haiting Sun; Che Wang; Dejing Shang (Molecular Biology Reports, 2024)

The effects and paths of regional industrial structure transformation on the fluctuation and quality of the marine fisheries economy in China - Bo Wang; Haiting Li; Pengyi Sun; Shaofeng Zhang; Hongzhi Zhang (Frontiers in Marine Science, 2023)
Industrial structure adjustment is an important component of China’s supply-side structural reforms. This study examines the effect and action path of regional industrial structure transformation, through the lens of advancement and rationalization, on the economic fluctuation and quality of the marine fishery industry. The results show that regional industrial structure advancement (rationalization) promotes (reduces) economic fluctuation. Regarding the action paths, regional industrial structure advancement (rationalization) has a U-shaped (inverted U-shaped) relationship with economic quality. The regional industrial structure advancement level is greater than 5.108 in China’s coastal areas and on the right side of the U shape. Thus, the evolution of the industrial structure in these areas is conducive to improving the economic quality of marine fisheries. Meanwhile, The degree of regional industrial structure rationalization has not reached the optimum level, and most areas are far from optimum level. This suggests that the structural dividends from industrial structure rationalization not fully released and need further regulation. In terms of the overall effect, regional industrial structure transformation can cause economic fluctuations in marine fisheries, with the main force originating from industrial structure advancement. The path of regional industrial structure transformation affecting economic quality of marine fisheries is non-linear. At present, the industrial structure advancement transformation can improve economic quality, but the industrial structure rationalization needs to be further adjusted.

Exploitation of nanocrystal suspension as an effective oral formulation for oxfendazole - Yuzhu Sun; Dongmei Chen; Ying Zhao; Kaixiang Zhou; Bao Zhang; Haiting Wang; Shuyu Xie (Drug Delivery and Translational Research, 2022)

Assessing climate change impacts on streamflow and sediment load in the upstream of the Mekong River basin - Di Ma; Budong Qian; Haiting Gu; Zhilin Sun; Yue‐Ping Xu (International Journal of Climatology, 2021)
Assessments of climate change impacts on streamflow and sediment processes are essential for developing science‐based sustainable watershed management plans. We assessed climate change impacts on streamflow and sediment load in the upstream of the Mekong River Basin, as a case study. Future climate scenarios including an ensemble‐mean climate scenario (EnM scenario) were generated based on 20 GCMs in CMIP5, using a stochastic weather generator (LARS‐WG) coupled with a distribution‐free shuffle procedure. The SWAT model was applied to simulate changes in streamflow and sediment load for the future period 2071–2100 under RCP8.5 with respect to the baseline period 1971–2000. Results show that mean monthly maximum and minimum temperature were projected to increase by all the 20 GCMs, with an ensemble‐mean increase of 4.6–5.7°C and 4.2–5.8°C across the 12 months, respectively. An increase in mean annual precipitation (3.4–55.8%) and streamflow (1.0–72.7%) was also projected by all GCMs. However, projected changes in sediment load were not consistent. One half of the GCMs projected an increase (5.2–53.2%) in annual sediment load while the other half projected a decrease (5.1%–43.2%). In each month, at least three‐quarters of the GCMs projected an increase in monthly streamflow. For monthly sediment load, an increase in May to July was projected by over half of the GCMs, while a decrease was projected by a majority of the GCMs for other months. Our results indicate large uncertainties in streamflow and sediment projections under climate change, demonstrating the need to use multi‐model ensembles in climate change impact studies. Moreover, it was found that the streamflow and sediment loads simulated using the EnM scenario were often close to the ensemble means simulated using the 20 GCMs, which implies that the single EnM scenario has the potential of effectively and efficiently estimating the ensemble means of projections in a multi‐model ensemble.

Do model parameters change under changing climate and land use in the upstream of the Lancang River Basin, China? - Di Ma; Yue-Ping Xu; Weidong Xuan; Haiting Gu; Zhilin Sun; Zhixu Bai (Hydrological Sciences Journal, 2020)

Analysis of Sealing and Leakage Performance of the Subsea Collet Connector with Lens-Type Sealing Structure - Feihong Yun; Gang Wang; Zheping Yan; Peng Jia; Xiujun Xu; Liquan Wang; Haiting Sun; Weifeng Liu (Journal of Marine Science and Engineering, 2020)
The contact mechanics model of the metal lens-type sealing gasket is established on the basis of Hertz theory on the macroscopical scale in this paper. The relationship among sealing width, contact pressure, and preload is solved. Based on the structural characteristics of the subsea collet connector, the self-locking characteristics are analyzed to determine the gain coefficient of the sealing structure for the loading thrust. On the microscopic scale, the contact characteristics of the turning lens-type sealing gasket and the hub structure are analyzed by the equivalent replacement of the peak cut coefficient of the one-dimensional sinusoidal wave. The influence of different leakage forms on sealing performance is discussed from both radial and circumferential leakage, and the leakage rate of the lens-type sealing structure is calculated. The hydrostatic pressure experiment of the subsea collet connector with lens-type sealing gasket is carried out, and the correctness of the theoretical analysis is verified from the results of the pressure maintaining, sealing width measurement, and preload conversion.

Functional effector memory T cells contribute to protection from superinfection with heterologous simian immunodeficiency virus or simian-human immunodeficiency virus isolates in Chinese rhesus macaques - Ming Sun; Huiwen Zheng; Yingpeng Xie; Bingxiang Li; Haiting Long; Ge Guo; Lei Guo; Jingjing Wang; Ruotong Ning; Yue Li; Longding Liu (Archives of Virology, 2017)